1988
DOI: 10.1136/vr.122.12.279
|View full text |Cite
|
Sign up to set email alerts
|

Avian cerebral tuberculosis

Abstract: Tuberculosis of the cerebrum was diagnosed in a 21-month-old chicken. Tuberculous lesions were also found in the liver, spleen, lungs, intestinal walls, skeletal muscles, bone marrow, heart wall and ovaries. Mycobacterium avium was isolated from the brain, liver and the lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Lesions found in the first and the second partridges (in liver, spleen and intestines) agree with those commonly seen in ATB (Thoen 1997). The necropsy findings of the third case could be considered unusual, but no tissue appears to be exempt from being affected (Thoen 1997), and other authors have reported nodules in muscle (Odiawo and Mukurira 1988). Microscope evaluation of the lesions revealed granulomas with central caseous necrosis and large amounts of acid-fast bacilli surrounded by epitheloid cells, giant cells, and lymphocytes.…”
Section: Resultsmentioning
confidence: 84%
“…Lesions found in the first and the second partridges (in liver, spleen and intestines) agree with those commonly seen in ATB (Thoen 1997). The necropsy findings of the third case could be considered unusual, but no tissue appears to be exempt from being affected (Thoen 1997), and other authors have reported nodules in muscle (Odiawo and Mukurira 1988). Microscope evaluation of the lesions revealed granulomas with central caseous necrosis and large amounts of acid-fast bacilli surrounded by epitheloid cells, giant cells, and lymphocytes.…”
Section: Resultsmentioning
confidence: 84%